2002
DOI: 10.1152/ajpendo.00078.2001
|View full text |Cite
|
Sign up to set email alerts
|

Myocellular triacylglycerol breakdown in females but not in males during exercise

Abstract: .-The resting content and use of myocellular triacylglycerol (MCTG) during 90 min of submaximal exercise [60% of peak oxygen uptake (V O2 peak)] were studied in 21 eumenorrheic female and 21 male subjects at different training levels [untrained (UT), moderately trained (MT), and endurance trained (END)]. Males and females were matched according to their V O2 peak expressed relative to lean body mass, physical activity level, and training history. All subjects ingested the same controlled diet for 8 days, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
186
6
9

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(235 citation statements)
references
References 48 publications
33
186
6
9
Order By: Relevance
“…The lack of data on glycaemic and insulinaemic responses to CHO with different GI values in women suggests that in many cases, the results from studies on male subjects are being directly applied to the female population. Several studies have shown that differences in substrate oxidation exist both at rest and during exercise between male and female subjects (Horton et al, 1998;Mittendorfer et al, 2002;Steffensen et al, 2002). The results of the present study are however very similar to those reported previously in male subjects who undertook exactly the same protocol .…”
Section: Discussionsupporting
confidence: 90%
“…The lack of data on glycaemic and insulinaemic responses to CHO with different GI values in women suggests that in many cases, the results from studies on male subjects are being directly applied to the female population. Several studies have shown that differences in substrate oxidation exist both at rest and during exercise between male and female subjects (Horton et al, 1998;Mittendorfer et al, 2002;Steffensen et al, 2002). The results of the present study are however very similar to those reported previously in male subjects who undertook exactly the same protocol .…”
Section: Discussionsupporting
confidence: 90%
“…Men have lower IMCL than women despite being more IR [38]. With endurance exercise, men exhibit lower lipid oxidation than women [39], and an acute exercise bout leads to muscle triacylglycerol breakdown in women but not in men [40]. Furthermore, PCOS women have more visceral fat than non-PCOS women, which decreases with exercise training in PCOS women only [26], again mimicking the response of visceral fat to exercise that occurs in men when compared with non-PCOS women [41].…”
Section: Discussionmentioning
confidence: 97%
“…Exercise at high intensities is more dependent on carbohydrates for fuel (7). Moderate exercise relies on plasma FFA as well, but also on muscle triglycerides (8,9). Because of the greater fat use, Flatt proposed that moderate exercise would be the optimal exercise for altering fat balance and, hence, controlling weight (6).…”
Section: Introductionmentioning
confidence: 99%